1996
DOI: 10.1165/ajrcmb.15.4.8879186
|View full text |Cite
|
Sign up to set email alerts
|

A transformed human tracheal gland cell line, MM-39, that retains serous secretory functions.

Abstract: Infection with the wild type SV40 virus was used to transform primary cultures of human tracheal gland serous (HTGS) cells. Over 80 different cell lines were obtained, but the majority had lost some of their epithelial and secretory features. However, one of these cell lines, MM-39, was shown to have conserved the physiologic characteristics of the genuine HTGS cells-i.e., the presence of cytokeratin, expression of cystic fibrosis transmembrane conductance regulator mRNA, a level of secretory leukocyte protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
1
34
1
Order By: Relevance
“…Fig. S3 shows that αBTX dose-dependently decreased forskolin-activated chloride efflux in MM39, a cell line derived from the normal human airway glandular epithelium and expressing WT-CFTR (23). It had no effect on KM4, a cell line derived from CF human tracheal glands and homozygous for the ΔF508 mutation (24), and decreased forskolin-activated chloride efflux in KM4*, derived from the KM4 cell line after transduction with the lentiviral vector expressing the WT-CFTR cDNA (25).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. S3 shows that αBTX dose-dependently decreased forskolin-activated chloride efflux in MM39, a cell line derived from the normal human airway glandular epithelium and expressing WT-CFTR (23). It had no effect on KM4, a cell line derived from CF human tracheal glands and homozygous for the ΔF508 mutation (24), and decreased forskolin-activated chloride efflux in KM4*, derived from the KM4 cell line after transduction with the lentiviral vector expressing the WT-CFTR cDNA (25).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the secretagogue agent ATP, proposed for CF therapy, acts on the human tracheal gland cell line MM39 by increasing protein secretion (32). This effect is mediated by cAMP generation and through calcium mobilization (32).…”
Section: Effect Of Mpb On Cftr Chloride Channel Activity Of and On Tmentioning
confidence: 99%
“…This effect is mediated by cAMP generation and through calcium mobilization (32). We examined the effect of MPB-07 on the secretion of the SLPI by MM39.…”
Section: Effect Of Mpb On Cftr Chloride Channel Activity Of and On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of genes to the airway results in gene expression primarily in lung epithelial cells, and the transgene is localised to the lung without much systemic distribution. The highest level of CFTR gene expression is found in the bronchial submucosal gland cells (Merten et al, 1996;Kammouni et al, 1999;Chow et al, 2000) and it was suggested that these glandular cells may be better reached by vasculature and systemic application of the vector rather than by the airways (Boucher, 1999 ;Kolb et al, 2006).…”
Section: Cftr Gene Transfer To the Airway Epitheliummentioning
confidence: 99%